Estudio de factibilidad para la creación de una empresa de elaboración y comercialización, de muñecos pedagógicos, hechos en tela en la ciudad de Cali - “Muñecos y algo más Ltda.” (2011)
Children are increasingly immersed in the world of video games, the internet and fashion dolls, which can affect their social and cultural development, as has been proposed as a business idea working with elaborate cloth dolls made in hand with pedagogical features, to meet the need to express feelings of love and promote the game as a learning activity, the game is the most important learning activity during the first years of life. When the child plays, learns about himself, about the properties of objects and people around them, while developing physical skills, cognitive, affective and social. Market research shows that although the world is awash in industrialized dolls and video games, stuffed cloth, they still stand out for its warmth, texture and tenderness that transmit these little buddies also shows that competition in the sector craft is based on quality, design a prince. The purpose of creating this company is to rescue the culture of art and meet the need of parents of children to play and learn together.